2013
DOI: 10.1007/s12149-013-0769-6
|View full text |Cite
|
Sign up to set email alerts
|

Integration of 2-deoxy-2-[18F] fluoro-d-glucose PET/CT into clinical management of patients with Wegener’s granulomatosis

Abstract: FDG with PET/CT is a valuable tool in the management of patients with WG for a more accurate clinical evaluation regarding disease extension and treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Besides, it is valuable in terms of showing unexpected involvement of the body. Ozmen et al showed that FDG PET/CT determined in 46% of patient population unexpected involvement areas such as great vessels, ear, spleen, kidney, duodenum, trachea and skin which were difficult to detect by conventional imaging procedures [31]. In our study, expect upper and lower respiratory tract and kidney, FDG PET/CT detected palata and prostate involvement.…”
Section: Discussionsupporting
confidence: 54%
“…Besides, it is valuable in terms of showing unexpected involvement of the body. Ozmen et al showed that FDG PET/CT determined in 46% of patient population unexpected involvement areas such as great vessels, ear, spleen, kidney, duodenum, trachea and skin which were difficult to detect by conventional imaging procedures [31]. In our study, expect upper and lower respiratory tract and kidney, FDG PET/CT detected palata and prostate involvement.…”
Section: Discussionsupporting
confidence: 54%
“…All active lesions showed decreased FDG uptake after treatment [ 47 ]. Ozmen and colleagues [ 48 ] also showed significantly decreased FDG uptake after complete remission of WG in their PET/CT study. FDG-PET/CT is more useful than traditional imaging studies, such as CT, for differentiating between active lesions and residual loci of inflammation in patients with WG.…”
Section: Part II the Usefulness Of Pet/ct Imaging In The Therapy Resmentioning
confidence: 93%
“…In addition, FDG-PET/CT can be combined with other imaging methods to inform selection of biopsy sites. Ozmen and colleagues [ 48 ] also reported PET/CT to be useful for detecting active lesions (except in the kidneys) and for identifying biopsy sites in patients with WG. FDG-PET/CT is more useful than traditional imaging studies, such as CT, for differentiating between active lesions due to WG and residual foci of inflammation.…”
Section: Part I the Usefulness Of Pet/ct Imaging In The Assessment Omentioning
confidence: 99%
“…In addition, this technique is beneficial for evaluating recurrence and spatial expansion of WG (11). Ozmen et al evaluated pulmonary and non-pulmonary involvement in a series of 13 WG patients by FDG PET/CT, and found evidence of involvement in the spleen and the adrenal glands in addition to the upper respiratory tract and the lungs (12). They evaluated the response to therapy by FDG PET/CT in only 2 out of 13 cases, and reported either complete resolution or decreased uptake on followup scans.…”
Section: Literature Review and Discussionmentioning
confidence: 99%